2016
DOI: 10.1007/s13632-016-0302-0
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Tilt Analysis of Electron Diffraction Patterns from Transition-Iron-Carbide Precipitates Formed During Tempering of 4340 Steel

Abstract: Fine-scale transition-iron-carbide precipitates in a lath martensitic microstructure of 4340 steel tempered at 200°C for 1 h were examined via imaging and electron diffraction techniques with a transmission electron microscope. Region-to-region variations were eliminated by analyzing a small volume of material (about 0.03 lm 3 ) at two tilt conditions. Geometric analyses showed that measured interplanar spacings compared favorably with accepted values from both epsilon-carbide and eta-carbide phases (within 1%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 44 publications
3
8
0
Order By: Relevance
“…The existence of g transition carbide is clearly observed in both conditions, in agreement with the TEM results shown in Figure 3. As noted previously, the unambiguous identification of g from e transition carbide by TEM is difficult, [14,[22][23][24] but these complementary HEXRD results corroborate the identification of g transition carbide by TEM in this work. It is also interesting to note that a small amount of cementite seems to be present in both conditions after austenitizing and quenching.…”
Section: B Microstructure After Fast and Slow Dilatometric Quenchingsupporting
confidence: 88%
See 1 more Smart Citation
“…The existence of g transition carbide is clearly observed in both conditions, in agreement with the TEM results shown in Figure 3. As noted previously, the unambiguous identification of g from e transition carbide by TEM is difficult, [14,[22][23][24] but these complementary HEXRD results corroborate the identification of g transition carbide by TEM in this work. It is also interesting to note that a small amount of cementite seems to be present in both conditions after austenitizing and quenching.…”
Section: B Microstructure After Fast and Slow Dilatometric Quenchingsupporting
confidence: 88%
“…Through careful microscopy and diffraction, Hirotsu and Nagakura showed that the transition carbide that forms in medium and high carbon steels during the first stage of tempering has an orthorhombic crystal structure, called g carbide. [20,21] Although there is some ambiguity in the distinction between the hexagonal transition carbide, e; and the orthorhombic transition carbide g, [22,23] several authors have suggested that diffraction patterns obtained after tempering are more consistent with g than e. [14,[23][24][25] Ha¨gg or v carbide has also been identified using TEM and diffraction to form as g disappears and cementite forms in later stages of tempering. [26,27] Mo¨ssbauer effect spectroscopy (MES) has been used as a valuable complement to TEM for the investigation of transition carbide formation during tempering.…”
Section: Introductionmentioning
confidence: 99%
“…For carbon-steels, Fe2C carbides can exist as either hexagonal ε-Fe2C (JCPDS card 36-1249) or 362 orthorhombic η-Fe2C (JCPDS card 37-999), both being transition carbides toward the formation of Fe3C at higher temperatures [26][27][28][29]. Both ε-Fe2C and η-Fe2C are very similar to each other, and earlier in the literature [5], ε-Fe2C was reported for Fe-C coatings.…”
Section: Discussed 361supporting
confidence: 77%
“…In a previous paper [1], the microstructure of quenched 4340 steel 1 tempered at 200°C for 1 h was shown to consist of martensite with, predominantly, transition-ironcarbide precipitates. Analysis of crystallographic aspects of the precipitates showed that the data could be interpreted as from a hexagonal epsilon-carbide phase or an orthorhombic eta-carbide phase [1,2].…”
Section: Introductionmentioning
confidence: 91%